UbiGDSS: a theoretical model to predict decision-makers’ satisfaction - Carneiro, João (2015)
The market globalization and the firms’ internationalization hinder the matching of the top managers’ agenda, making it difficult to meet in the same space or time. On the one hand, the appearance of Ubiquitous Group Decision Support Systems (UbiGDSS) enabled individuals to gather and make decisions in different spaces at different times, but on the other hand, originated problems related to the lack of human interaction. To understand how the arguments used can influence each of the decision-makers, what is their satisfaction regarding the decision made, and other affective issues such as emotions and mood, are some examples of that lack. In order to try to overcome this lack, we propose a theoretical model that is specially designed for agents, helping to understand the interactions impact on each agent and their satisfaction with the decision made.